2017
DOI: 10.46886/ijarp/v4-i1/3492
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Mental Health among Orphan and Non-Orphan Adolescents

Abstract: The study aims to identify the differences of mental health among orphan and non-orphan adolescents in Malaysia. This study used a quantitative method. The sample comprised of 240 orphans and 240 non-orphan adolescents, aged 13 to 17 years old selected through multistage sampling. The validated Malay version of Depression, Anxiety, Stress Scale 21 Item (DASS21) used in this study to measure mental health among the orphan and non-orphan adolescents. The findings showed that there have differences of mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 22 publications
1
17
0
3
Order By: Relevance
“…In addition, Huynh et al (2019) reported that the experience of growing up at an orphanage has a profound impact on orphans' psychosocial development and later mental health functioning. Similar results were found in other studies, indicating that compared with noninstitutionalized children, orphans scored significantly lower on mental health and higher on emotional problems such as anxiety, depression, and stress (Atwine et al, 2005;Sahad et al, 2018). A semistructured interview conducted on orphans in their late adolescence in orphanages reported negative emotional experiences in aspects of loneliness, entrapment, boredom or idleness, deprivation, rejection, and helplessness, which were related to peer discrimination, social isolation, detachment from biological parents, and emotional neglect from the caregivers (Boadu et al, 2020).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In addition, Huynh et al (2019) reported that the experience of growing up at an orphanage has a profound impact on orphans' psychosocial development and later mental health functioning. Similar results were found in other studies, indicating that compared with noninstitutionalized children, orphans scored significantly lower on mental health and higher on emotional problems such as anxiety, depression, and stress (Atwine et al, 2005;Sahad et al, 2018). A semistructured interview conducted on orphans in their late adolescence in orphanages reported negative emotional experiences in aspects of loneliness, entrapment, boredom or idleness, deprivation, rejection, and helplessness, which were related to peer discrimination, social isolation, detachment from biological parents, and emotional neglect from the caregivers (Boadu et al, 2020).…”
supporting
confidence: 87%
“…Attachment styles formed during early interactions with the caregivers plays a significant role in the growth of children and have a lasting life‐long impact, according to the perspective of social development by the attachment theory of Bowlby (1969). Due to the deprived attachment to parental attention and love, orphans have difficulties in forming a stable and secure attachment style (Atwine et al, 2005; Cluver et al, 2009; Sahad et al, 2018), thus potentially leading to a long‐term, negative impact on orphans' wellbeing (Ntuli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, although there are studies that examine psychological well-being among orphans, most of these studies in Malaysia focus more on aspects of clinical psychological well-being such as stress, anxiety, and depression only (Mohammadzadeh et al, 2019;2018a;Sahad et al, 2018). Moreover, studies that examine the relationship between life satisfaction, emotional intelligence, and self-esteem with psychological wellbeing are also very little studied by researchers in Malaysia and overseas (Batool and Shehzadi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In prior research, both depression and underage initiation of selling sex have been found to be associated with socioeconomic and demographic variables including income, 15,16 food insecurity, 17-19 and orphanhood. 20,21 Depression and selling sex while underage have both been linked to healthcare issues such as perceiving or experiencing sex work-related stigma in healthcare settings 17,22 and not being tested for HIV or aware of one’s HIV status. 6,23 Behavioral risk factors, including not carrying condoms 5,24 and reporting condom use errors such as slipping and breaking 25,26 are related to both depression and underage initiation of selling sex.…”
Section: Introductionmentioning
confidence: 99%